Snapshot versus continuous documentation of pharmacists’ interventions: are snapshots worthwhile? - Ramadaniati, Hesty Utami; Lee, Ya Ping; Hughes, Jeff (Society of Pharmacy Practice and Research, 2014)
Background: The documentation of pharmacists’ interventions is important but there are limited studies evaluating the different methods of documentation. Aim: To compare the nature of pharmacists’ interventions documented during snapshots versus direct observation in a paediatric hospital and to gather pharmacists’ opinions on the utility of the different documentation methods. Method: The pattern and rates of pharmacists’ interventions from the snapshot reports and direct observation were compared across five study wards. The snapshots represented pharmacists’ self-reported interventions over a period of 5 days. The researcher observed and documented pharmacists’ interventions for 35–37 non-consecutive days. A focus group discussion was conducted to gather pharmacists’ opinions on the documentation methods. Results: A total of 398 interventions were documented by pharmacists during three snapshots with ‘clarification of medication orders’ being the commonest type of intervention. A total of 982 pharmacists’ interventions were documented during direct observation. The overall rate of pharmacists’ interventions documented during observation was not significantly different compared to that of the snapshots (p = 0.054). However, the rate of active interventions (i.e. interventions leading to a change in drug therapy) was significantly higher (p = 0.002) during direct observation, and the pattern of interventions was significantly different. From the focus group discussion, participants felt that the snapshot reports were an inadequate representation of pharmacists’ clinical activities.Conclusion: Documentation of pharmacists’ active interventions during snapshots was not representative of those documented during observation. This suggests that snapshot data may underestimate the impact of pharmacists’ interventions in minimising medication misadventure amongst paediatric inpatients.